Pengendalian Persediaan Bahan Baku Menggunakan Metode Min-Max Stock Pada Produk Keramik Lantai PT AB - Damayanti, Atika; Debora, Fransisca; S, Ade Momon; Kabul, Putri Meiliawati (Fakultas Teknik Universitas Tulang Bawang, 2026)
In production systems, optimal raw material inventory management is crucial in maintaining production continuity. Excess inventory will increase storage costs, while inventory shortages can cause production disruptions and lost sales opportunities. Therefore, in this study, the aim is to determine the control of raw material inventory in the manufacture of floor ceramics, namely Andesite by utilizing the min-max stock method, where later in the data processing, forecasting is carried out with time series methods such as Double Exponential Smoothing, Moving Average, Weight Moving Average, and Linier Regression. Based on the results of data processing, the forecasting model using Linear Regression was selected because it has the smallest Mean Square Error (MSE) value, then the calculation results are used to determine the amount of safety stock, minimum and maximum stock, reorder point to order frequency. The calculation results obtained inventory value produces a minimum stock value of 658,182 KG, and a maximum stock of 1,276,183 KG. The quantity in one order is 1,236,001 KG with an order frequency of 60 times. The research results obtained can be used as an inventory policy at PT AB in reducing stockouts on Andesite raw materials using the Min-max stock method. Keywords: Ceramic Floor Raw Materials, Inventory Control, Min-max stock Method